Autobiografie filozofów - Lubas-Bartoszyńska, Regina (Przestrzenie Teorii, 2010)
Lubas-Bartoszyńska Regina, Autobiografie filozofów [Autobiographies of philosophers]. „Przestrzenie Teorii” 13. Poznań 2010, Adam Mickiewicz University Press, pp. 55-75. ISBN 978-83-232-2176-0. ISSN 1644-6763. The article Autobiographies of philosophers is composed of three parts. The first part presents the history of philosophic autobiography since antiquity and spiritual autobiography of Saint Augustine, through “Confessions” of J.J. Rousseau – the creator of modern autobiography, Pascal, G. Berkeley and S. Kierkegaard, back to “Ecce homo” of Nietzsche. The second part presents selected autobiographies of philosophers of the 20th century like an autobiography of B. Russell (three volumes), M. Bierdiaev, K. Jaspers. The third part is an interpretation of the intellectual autobiography of P. Ricoeur, in which the author reproduces history of intellectual and philosophic development and shows the dissimilarity of “idem” to his own identity.